Molecular mechanism of high-pressure processing for improving the quality of low-salt Eucheuma spinosum chicken breast batters. (1st February 2019) - He, Dan; Wang, Xixi; Ai, Mingyan; Kong, Yuting; Fu, Lingyun; Zheng, Baodong; Song, Hongbo; Huang, Qun
ABSTRACT: To confirm the role of high-pressure processing in enhancing the quality of Eucheuma spinosum chicken breast batters, low-field nuclear magnetic resonance, scanning electron microscopy and Raman spectroscopy were used to explore the effect of E. spinosum and high-pressure processing on water migration, protein conformation, and microstructure in chicken breast batters. The water-holding capacity, surface hydrophobicity, and reactive sulfhydryl group content significantly increased as the pressure increased (0.1 to 300 MPa), while the peak ratio of non-flowable water ( T 22 ) decreased ( P > 0.05). The secondary structure composition changed significantly, and the β -sheet, β -turn, and random coil content significantly increased ( P < 0.05) as the α -helix content decreased. The –OH stretching vibration (3, 100 to 3, 500 cm −1 ) was shifted to higher wavenumbers, and the number of hydrogen bonds in each water molecule increased. The scanning electron microscopy images reveal that proper pressure produced a dense network structure with small cavities. Moreover, these characteristics were further enhanced when E. spinosum was added from 0 to 0.4%. Overall, this paper could provide crucial theoretical support for the application of high-pressure processing of low-salt seaweed chicken breast.